2000
DOI: 10.1046/j.1365-2702.2000.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Older people and laxative use: literature review and pilot study report

Abstract: This study explored older adults' perceptions of constipation, and the measures taken if they believed themselves to be afflicted by this condition. The paper provides an overview of the current literature surrounding laxative use, followed by a discussion of the pilot study and its findings. The objectives of the pilot study were to establish older people's definitions of the term 'constipation'; identify prescribed laxatives, over-the-counter laxatives, and home remedies used by older people to manage consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
0
31
0
2
Order By: Relevance
“…The physical ailments included feeling sick, having cramps and bloating, and enduring strenuous and painful defecations, and these ailments have been described in previous studies. [17,22] The women did not describe constipation as a reminder of death, as was found by [18] Friedrichsen and Erichsen, [18] but constipation seemed to affect their lives in a comprehensive manner. It seems reasonable to compare our findings with those of Dennison et al, [23] who indicated that people with constipation have a low quality of life in relation to their health.…”
Section: Discussion Of the Findingsmentioning
confidence: 89%
See 2 more Smart Citations
“…The physical ailments included feeling sick, having cramps and bloating, and enduring strenuous and painful defecations, and these ailments have been described in previous studies. [17,22] The women did not describe constipation as a reminder of death, as was found by [18] Friedrichsen and Erichsen, [18] but constipation seemed to affect their lives in a comprehensive manner. It seems reasonable to compare our findings with those of Dennison et al, [23] who indicated that people with constipation have a low quality of life in relation to their health.…”
Section: Discussion Of the Findingsmentioning
confidence: 89%
“…In our recent study, [16] one women described her relationship to her bowel almost as a war: she was fighting and almost punishing the bowel with laxatives, which resulted in a sore bowel, but this was the only way she knew to handle the situation. Another study [17] explored older persons' (> 65 years of age) experiences of being constipated, in which they reported unpleasant feelings of bloating, cramps and nausea that affected their health and well-being. They related being preoccupied with their bowels and needing to have immediate access to a toilet, which hampered social activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians consider the frequency of defecation episodes, stool weight, colonic transit time, and anorectal manometry as proxy measures for constipation [5,6] . A commonly held belief amongst clinicians is that the problem of constipation is more imagined than real, as "the great majority of those complaining of constipation have a bowel motion (movement) more frequently than three times a week" [7] .…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 2, numerous factors may contribute to the development of constipation [6][7][8][9]66,67] . Though bowel transit time and frequency of bowel movements do not change with aging, a number of comorbid conditions may contribute to the development of constipation [66] .…”
Section: Pathophysiology Of Constipation In the Older Adultmentioning
confidence: 99%